Colored solar façades for buildings. (September 2017) - Jolissaint, Nicolas; Hanbali, Rafic; Hadorn, Jean-Christophe; Schüler, Andreas
Abstract: Solar energy is a prime way to reach net zero energy buildings. Addressing buildings' energy needs is a priority because buildings are the largest demander of energy (followed by industry then transport). However, harvesting energy from solar farms, implies covering large areas with standard black or blue solar modules, which is generally not well accepted by the stakeholders. If architectural coherence is to be preserved, building envelopes cannot simply be covered with black panels with visible cells and contact bars. Today, panels of different colors are available to integrate solar energy smoothly into the built environment. However, while a choice of colors is good news for architecture, it should not cause excessive energy losses. The Kromatix panels presented in this paper are covered by glass that combines effects of diffuse surfaces and interference filters. With a minimal loss of efficiency, these panels pave the way to new considerations in solar architecture.